Summary of Sloan symposium: healthy buildings 2015-Europe. Issue 1 (December 2015) - Levin, Hal; Täubel, Martin; Hernandez, Mark
Abstract The Sloan Symposium, "Microbiology of the Indoor Environment, " was held to facilitate dialog on biological research between scientists and practitioners in the field which was complementary to the adjoining activities of the ISIAQ Healthy Buildings Europe conference, Eindhoven, Netherlands, on 20–21 May 2015. Multi-media archives of these special adjunct proceedings are presented.